Cognitive dysfunction, diabetes mellitus 2 and arterial hypertension: Sequelae up to one year of COVID-19. Issue 52 (March 2023) - Fernández-Ortega, Miguel Á.; Ponce-Rosas, Efrén R.; Muñiz-Salinas, Daniel A.; Rodríguez-Mendoza, Omar; Nájera Chávez, Paola.; Sánchez-Pozos, Verónica; Dávila-Mendoza, Rocío; Barrell, Alan E.
Abstract: Background: Covid symptoms reflect its multisystem nature, in addition to its positive relationship between the severity of the condition and the severity of the long COVID. Objective: To identify the factors associated with the prevalence of SEQUELAE DUE TO COVID-19 one year after their hospital discharge due to severe pneumonia. Method: Longitudinal, analytical, prospective and comparative study. 71 covid-19 pneumonia survivors were followed. Two telephone interviews were conducted to each patient; the first at 5 months of discharge and the second at 12 months from the mentioned date. We included questions of 40 symptoms, in addition to the questioning of diabetes mellitus and/or systemic hypertension with a mentioned onset during the hospitalization or after hospital discharge due to COVID-19. Results: Of the 37 patients without complications and without comorbidities prior to hospitalization, 11 (29.7%) developed arterial hypertension during or after discharge and 17 (45.9%) developed diabetes mellitus before five months. Short-term memory loss was an upward sequel in the two measurements, 24.3% and 41.9% respectively. Conclusions: Type 2 diabetes mellitus and high blood pressure detected at five months was temporary and reversed in many cases at twelve months. It will be important to deepen the study of brain damage and cognitive dysfunction, characterized by memory loss.